A Secreted Peptide and Its Receptors Shape the Auxin Response Pattern and Leaf Margin Morphogenesis - Tameshige T.; Okamoto S.; Lee Js; Aida M; Tasaka M; Torii Ku; Uchida N
Secreted peptides mediate intercellular communication [1, 2]. Several secreted peptides in the EPIDERMAL PATTERNING FACTOR-LIKE (EPFL)family regulate morphogenesis of tissues, such as stomata and inflorescences in plants [3-15]. The biological functions of other EPFL family members remain unknown. Here, we show that the EPFL2 gene is required for growth of leaf teeth. EPFL2 peptide physically interacts with ERECTA (ER)family receptor-kinases and, accordingly, the attenuation of ER family activities leads to formation of toothless leaves. During the tooth growth process, responses to the phytohormone auxin are maintained at tips of the teeth to promote their growth [16-19]. In the growing tooth tip of epfl2 and multiple er family mutants, the auxin response becomes broader. Conversely, overexpression of EPFL2 diminishes the auxin response, indicating that the EPFL2 signal restricts the auxin response to the tooth tip. Interestingly, the tip-specific auxin response in turn organizes characteristic expression patterns of ER family and EPFL2 by enhancing ER family expression at the tip while eliminating the EPFL2 expression from the tip. Our findings identify the novel ligand-receptor pairs promoting the tooth growth, and further reveal a feedback circuit between the peptide-receptor system and auxin response as a mechanism for maintaining proper auxin maxima during leaf margin morphogenesis.
Keywords: PEPTIDES; INTERCELLULAR COMMUNICATION